2022
DOI: 10.1186/s13024-022-00515-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based biomarkers of inflammation in amyotrophic lateral sclerosis

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a devastating neurodegenerative disease in which many processes are detected including (neuro)inflammation. Many drugs have been tested for ALS in clinical trials but most have failed to reach their primary endpoints. The development and inclusion of different types of biomarkers in diagnosis and clinical trials can assist in determining target engagement of a drug, in distinguishing between ALS and other diseases, and in predicting disease progression rate, drug responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 97 publications
(190 reference statements)
3
31
0
Order By: Relevance
“…A recent study found that a decrease in the compound muscle action potential (CMAP) amplitude in the phrenic nerve was associated with increased IL-6 levels in ALS ( 46 ). In corroboration with previous studies, it also reported that changes in peripheral blood PaO 2 affected fluctuations in IL-6 levels in the serum and CSF of ALS ( 47 ). Therefore, the level of IL-6 reflects the severity of respiratory function involvement in patients with ALS to some extent ( 46 , 47 ).…”
Section: Cytokinessupporting
confidence: 91%
See 2 more Smart Citations
“…A recent study found that a decrease in the compound muscle action potential (CMAP) amplitude in the phrenic nerve was associated with increased IL-6 levels in ALS ( 46 ). In corroboration with previous studies, it also reported that changes in peripheral blood PaO 2 affected fluctuations in IL-6 levels in the serum and CSF of ALS ( 47 ). Therefore, the level of IL-6 reflects the severity of respiratory function involvement in patients with ALS to some extent ( 46 , 47 ).…”
Section: Cytokinessupporting
confidence: 91%
“…In corroboration with previous studies, it also reported that changes in peripheral blood PaO 2 affected fluctuations in IL-6 levels in the serum and CSF of ALS ( 47 ). Therefore, the level of IL-6 reflects the severity of respiratory function involvement in patients with ALS to some extent ( 46 , 47 ). Simultaneously, Sun et al.…”
Section: Cytokinessupporting
confidence: 91%
See 1 more Smart Citation
“…For example, immune cell-deficient SOD1 G93A mice progressed faster to the end stage compared to their immune-competent littermates [ 45 , 46 ], and a passive transfer of T cells (T eff and T reg ) to SOD1 G93A mice was able to delay loss of motor function and extended survival [ 47 ]. Furthermore, reductions as well as elevations in a range of immune cell subpopulations have been shown for blood from ALS patients (recently reviewed by [ 48 ]). In our study, we found that, on a gross cellular level, lymphocyte and granulocyte populations did not show disease- or treatment-related changes or adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…• Elevated metalloproteinase-9 (MMP-9) [2] • Increased levels of MMP-2 [3,4] • The loss of motor neurons is the primary neuropathological hallmark of ALS [20] • Mutations in SOD1 [28] • Elevated Extracellular matrix metalloproteinase inducer (EMMPRIN) [3] • Decrease in the expression of human leukocyte antigen by ALS monocytes [21] • Mutations in tardbp (TDP-43) [29][30][31] • Elevated level of Inflammation Markers, like MCP-1, TNFa, IL-6, IL-7, Eotaxin, GM-CSF, OX40, etc. [5][6][7][8][9] • An increase in the amount of natural killer T lymphocytes [22] • Binding of mutant C9orf72 to trimethylated histones was detected in ALS mononuclear cells [32] • Hypermetabolism, and hyperlipidemia [10][11][12] • High neutrophil-to-lymphocyte ratio [23] • Mutations in FUS gene [33][34][35][36] • High concentrations of lead in blood and in the CSF [13][14][15] • Decrease in the number of regulatory T cells [21,22] • Vesicle-associated membrane proteinassociated protein B (VAPB) [37] • Low level of type I procollagen [16][17][18][19].…”
Section: Biochemical Biomarkers Cellular Biomarkers Genetic Biomarkersmentioning
confidence: 99%